Hubungan Stress dengan Kadar Gula Darah Sewaktu pada Mahasiswa Rekognisi Pembelajaran Lampau (RPL) di Poltekkes Kemenkes Palangka Raya - Natalansyah Natalansyah; Debora Kartika Sari; Wijaya Atmaja Kasuma (Jurnal Surya Medika (JSM), 2020)
Stress is the condition of an individual who experiences excessive emotional demands, a time problem that makes it difficult to manage efficiently all aspects of life (Richard, 2010). In someone with mild and moderate levels of stress will experience changes in blood sugar levels. This study examines stress levels and random blood sugar levels in nursing students. The purpose of this study was to identify respondent characteristics, stress levels, random blood sugar levels and the relationship between stress levels and random blood sugar levels at the health Polytechnic of Palangka Raya. The research method respondents (f = 39) was assessed using the Perceived Stress Scale -10 questionnaire to measure stress level. Glucometer was used for checking the random blood sugar levels. Chi-Square test was used to determine the relationship between the two variables, results from 39 respondents who had moderate stress levels, 27 respondents had high blood sugar levels of 23 (85.2%) and mild stress levels as many as 12 respondents with normal blood sugar levels 7 (58.3); There is a correlation between stress and random blood sugar levels in Secondary Learning Recognition (RPL) students of the Nursing Department Class II at Health Polytechnic of Palangka Raya with ρ value <0.005.